Changes in clinical condition of the eye and in parameters of cell and humoral immunity in iridocyclitis patients under the influence of anti-viral allokin-alpha (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Iridocyclitis, inflammatory eye disease of the uvea, is a topical issue not only in clinical but social regard, considering its high prevalence and disability rates.Purpose. To study changes in the clinical condition of the eye and the state of cellular and humoral immunity in iridocyclitis patients under the influence of allokin-alpha anti-viral drugs.Material and Methods. We observed 41 patients (41 eyes) with acute and chronic iridocyclitis who underwent anti-viral allokin-alpha treatment at Inflammatory Eye Pathology Department at SI “The Filatov Institute of Eye Diseases and Tissue Therapy”.Results. Over the treatment course we observed a significant increase in immunoregulatory index from 1.16% to 2.00%; a relative T-lymphocyte count increased from 38.2±0.5% to 63.4±1.2% and a relative CD-19 lymphocyte count decreased from 24.4% to 21.8%, which reached normal parameters at 18 days after treatment onset. The treatment resulted in VA improvement.Conclusions. Using allokin-alpha anti-viral drug enables to raise treatment success in viral iridocyclitis patients and to improve VA against the background of inflammatory process reduction.
Keywords: iridocyclitis; allokin-alpha